Exploring the Meaning of Ichnography at the Cheng Ho Mosque - Endah Wulandari (Sean Institute, 2025)
Cheng Hoo Mosque located on Jl. Raya Purbalingga, Selaganggeng Village, Mrebet District, Purbalingga is a mosque building that has a shape resembling a Chinese temple building with a Chinese architectural style. The architecture of the Cheng Hoo Mosque is present to color certain communities dynamically bringing different nuances, because this mosque is an interesting expression to review. Cheng Hoo Mosque in Purbalingga is an interesting research object to be studied related to the meanings contained in its architectural and interior forms. This research object, besides being unique and interesting, also contains aesthetic values displayed through symbols and icons in its architecture and interior. The results of research, analysis, and discussion of the Cheng Hoo Mosque in Purbalingga with an Iconography approach through three stages of analysis, namely pre-iconography, iconography, and iconological interpretation. This mosque shows the artistic motifs in it to represent the aesthetic form with a fantasy style. The theme in the basic concept of Chinese ethnic conflict. The symbolic value contained in the work is to inform that there is a collaboration between China and the archipelago